Mediation of Cardiac Macrophage Activity via Auricular Vagal Nerve Stimulation Ameliorates Cardiac Ischemia/Reperfusion Injury - Chung, Chee Hooi; Bretherton, Beatrice; Zainalabidin, Satirah; Deuchars, Susan A.; Deuchars, Jim; Mahadi, Mohd Kaisan (Frontiers in Neuroscience, 2020)
Background: Myocardial infarction (MI) re-perfusion therapy causes paradoxical cardiac complications. Following restoration of blood flow to infarcted regions, a multitude of inflammatory cells are recruited to the site of injury for tissue repair. Continual progression of cardiac inflammatory responses does, however, lead to adverse cardiac remodelling, inevitably causing heart failure. Main Body: Increasing evidence of the cardio-protective effects of both invasive and non-invasive vagal nerve stimulation suggesting that these may be feasible methods to treat myocardial ischemic re-perfusion injury via anti-inflammatory regulation. The mechanisms through which auricular vagal nerve stimulation controls inflammation are yet to be explored. In this review, we discuss the potential of autonomic nervous system modulation, particularly via the parasympathetic branch, in ameliorating myocardial infarction. Novel insights are provided about activation of the cholinergic anti-inflammatory pathway on cardiac macrophages. Acetylcholine binding to the α7 nicotinic acetylcholine receptor (α7nAChR) expressed on macrophages polarizes the pro-inflammatory into anti-inflammatory sub-types. Activation of the α7nAChR stimulates the STAT3 signalling pathway. This inhibits the secretion of pro-inflammatory cytokines, limiting ischemic injury in the myocardium and initiating efficient reparative mechanisms. We highlight recent developments in the controversial auricular vagal neuro-circuitry and how they may relate to activation of the cholinergic anti-inflammatory pathway. Conclusion: Emerging published data suggest that auricular vagal nerve stimulation is an inexpensive healthcare modality, mediating the dynamic balance between pro- and anti-inflammatory responses in cardiac macrophages and ameliorating cardiac ischemic re-perfusion injury.